Focused echocardiography and lung ultrasound protocol for guiding treatment in acute heart failure - Jonas Öhman; Veli-Pekka Harjola; Pasi Karjalainen; Johan Lassus (published by John Wiley & Sons Ltd on behalf of the European Society of Cardiology, 2022)
Conclusions
The CaTUS-guided therapy for AHF resulted in greater decongestion during shorter hospitalization without increased adverse events in this small pilot study and might be associated with a better post-discharge prognosis.